First Principles Study of Electronic and Optical Properties of Cadmium-Tin-Oxide - Adel Bandar Alruqi (Inorganics)
Cadmium-tin-oxide (CTO), also referred to as cadmium stannate (Cd2SnO4), is known for its interesting electrical, electronic, and optical properties, making it useful in various applications such as in transparent conducting oxides for optoelectronic devices and also in photovoltaic applications. While its properties have been investigated experimentally, there is not much record in the literature on the computational study of the electronic and optical properties of CTO. This study employed density functional theory to explore the two properties of CTO. The hybrid functionals were used to widen the band gap from 0.381 eV (for PBE) to 3.13 eV, which replicates the experimental values very well. The other properties obtained were a refractive index of 2.53, absorption coefficient of 1.43 × 104 cm−1, and dielectric constant of 6.401 eV. The optical energy loss of 0.00691 that was investigated for the first time in this work adds to the literature on the properties of CTO. However, the electrical properties of CTO, which also play a key role in the working of optoelectronic devices, need to be investigated.